Comparative effect of the sites of anterior cervical pressure on the geometry of the upper esophageal sphincter high‐pressure zone. (23rd May 2017) - Mei, Ling; Jiao, Hongmei; Sharma, Tarun; Dua, Arshish; Sanvanson, Patrick; Jadcherla, Sudarshan R.; Shaker, Reza
Abstract : Objectives/Hypothesis: External cricoid pressure is increasingly used to augment the upper esophageal sphincter (UES). Our objective was to determine the effect of 1) pressures applied to cricoid, supracricoid, and subcricoid regions on the length and amplitude of the UES high‐pressure zone (UESHPZ), and 2) the external cricoid pressure on lower esophageal sphincter (LES) tone. Study Design: Case‐control study. Methods: We studied 11 patients with supraesophageal reflux (mean age 58 ± 12 years) and 10 healthy volunteers (mean age 47 ± 19 years). We tested 20, 30, and 40 mm Hg pressures to cricoid, 1 cm proximal and 1 cm distal to the cricoid. In an additional 15 healthy volunteers (mean age 46 ± 23 years), we studied the effect of external cricoid pressure on LES tone. UES and LES pressures were determined using high‐resolution manometry. Results: There was significant increase of UESHPZ length with application of pressure at all sites. The increase of UESHPZ length was relatively symmetric, more orad, and more caudad when the pressure was applied at the cricoid, supracricoid, and subcricoid levels, respectively. The magnitude of pressure increase was greatest at the middle and orad part of the UESHPZ when the pressure was applied at the cricoid and supracricoid levels, respectively. The corresponding magnitude of increase in the caudad part of the UESHPZ was not observed with pressure at the subcricoid level. There was no change of the LES pressure with application of cricoid pressure. Conclusions: The effect of external pressure on the UESHPZ is site dependent. Subcricoid pressure has the least effect on UESHPZ. External cricoid pressure at 20 to 40 mm Hg has no effect on the LES pressure. Level of Evidence: 3b. Laryngoscope, 127:2466–2474, 2017